Understanding the synthetic pathway of a single-phase quarternary semiconductor using surface-enhanced raman scattering : a case of Wurtzite Cu2ZnSnS4 nanoparticles - Tan, Joel Ming Rui (2014)
Single-phase Cu2ZnSnS4 (CZTS) is an essential prerequisite toward a high-efficiency thin-film solar cell device. Herein, the selective phase formation of single-phase CZTS nanoparticles by ligand control is reported. Surface-enhanced Raman scattering (SERS) spectroscopy is demonstrated for the first time as a characterization tool for nanoparticles to differentiate the mixed compositional phase (e.g., CZTS, CTS, and ZnS), which cannot be distinguished by X-ray diffraction. Due to the superior selectivity and sensitivity of SERS, the growth mechanism of CZTS nanoparticle formation by hot injection is revealed to involve three growth steps. First, it starts with nucleation of Cu2–xS nanoparticles, followed by diffusion of Sn4+ into Cu2–xS nanoparticles to form the Cu3SnS4 (CTS) phase and diffusion of Zn2+ into CTS nanoparticles to form the CZTS phase. In addition, it is revealed that single-phase CZTS nanoparticles can be obtained via balancing the rate of CTS phase formation and diffusion of Zn2+ into the CTS phase. We demonstrate that this balance can be achieved by 1 mL of thiol with Cu(OAc)2, Sn(OAc)4, and Zn(acac)2 metal salts to synthesize the CZTS phase without the presence of a detectable binary/ternary phase with SERS.